Posebne zmožnosti slovenščine znotraj glagolsko-udeleženskega razmerja - Žele, Andreja (Slavistična revija, 2012)
The article aims to shed light on the concept of ergativity in Slovene. It also points out the importance of the participant roles and/or the so-called deep cases and diathetic capabilities of Slovene in general from the standpoint of the secondary, i.e., non-typical, ergative language system and ergative sentence structure.
Keywords: ergativni sklon; grammar; jezikoslovje; linguistics; Slovene; slovenščina; slovnica; stavčna zgradba; udeleženec